Study on Micro-vacuum Storage Facility and Fresh-keeping of Laiyang Pear (Zhileng xuebao)
Micro-Vacuum storage facility is a mild vacuum-storage apparatus,which was on the basis of conventional vacuum-storage,by adding a flexibility air sac to overcome the stress of facility wall and the higher weight loss under vacuum storage.The structure principle and main component of micro-vacuum storage were introduced,with the emphasis on the materials and functions about air sac,vacuum systems and control systems device.It also discussed the fresh-keeping effect of Laiyang pear on this micro-vacuum stora...